Vanillin as eco-friendly corrosion inhibitor for aluminum immersed in 0.5 M H2SO4 - América María Ramírez-Arteaga; Martha Patricia Hernández-Valencia; Rene Guardián-Tapia; Ana Karen Gálvez-Larios; José Gonzalo González-Rodríguez; Roy López-Sesenes (Scientific Reports)
Abstract The possibility of using Vanillin as an eco-friendly corrosion inhibitor for Al in 0.5 M H2SO4 has been evaluated, examining concentrations ranging from 0 to 10 mM at 25, 40, and 60 °C. Results indicate that Vanillin is a mixed corrosion inhibitor. Its inhibitory effect can be attributed to aldehyde functional groups forming a protective layer by reacting with Al3+ ions, which are chemisorbed onto the metal’s surface, as was demonstrated via SEM analysis of the metal surface. The I corr and R p values estimated from the electrochemical characterization tend to improve in the presence of Vanillin. However, inhibition efficiency is affected by temperature, resulting in lower values. Also, the weight loss analyses demonstrated that Vanillin is desorbed over time and temperature. The SEM micrographs taken after weight loss show an aluminum surface with several pits in the absence of inhibitor. Otherwise, EDS analyses show the presence of carbon, confirming the Vanillin adsorption on the metal surface.